Learning Design Innovation Based on Tri N and STEAM in Developing 21st Century Skills for Elementary School Students - Pardimin; Ana Fitrotun Nisa; Nurul Hikmah (Jurnal Ilmiah Sekolah Dasar, 2023)
The low level of 21st-century skills possessed by elementary school students. These 21st-century skills need to be acquired early so that students can be independent, survive, and adapt to the times. This study aims to innovate learning designs based on Tri N and STEAM to develop 21st century skills of elementary school students. The tools developed include lesson plans, student worksheets, and 21st century skills assessment instruments. The learning tool development process consists of analysis, design, development, implementation, and evaluation stages. The research subjects were teachers and grade six students. Data collection techniques using questionnaires, interview sheets, observation sheets and documentation. Data analysis techniques were carried out through descriptive analysis and quantitative analysis. The results showed that Tri N and STEAM-based learning tools developed had integrated characteristics with niteni, niroake, nambahake steps, and activities designed to integrate aspects of science, technology, engineering, art and mathematics. The results of validation of learning tools obtained an average of 3,87 with a very good category. The results of the effectiveness of the developed tools show that the developed tools are effective in developing 21st century skills of students. In a limited trial, there was an increase in the initial average from 2,333 to 3,659 with very good criteria. In the wide trial, there was an increase from the initial average of 2,842 to 3,747 with very good criteria so it can be concluded that the Tri N and STEAM based learning device innovation is effective in developing 21st century skills of elementary school students. based on the data above, it is concluded that Tri N and STEAM-based learning design innovations can develop 21st century skills of elementary school students.